2013
DOI: 10.1007/s10899-013-9405-6
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure and Psychometric Properties of the Italian Version of the Gambling Related Cognitions Scale (GRCS-I)

Abstract: The past decade has witnessed an expanded accessibility and popularity of gambling worldwide, and in Italy the phenomenon significantly increased. Nevertheless, little is known about the role of gambling cognitions among Italian individuals, and few scales assessing problem gambling have been validated. The purpose of the present study was to examine and validate the Gambling Related Cognitions Scale-Italian version (GRCS-I), based on the 23-item Gambling Related Cognitions Scale (GRCS). Two-tailed t tests, AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Similarly, there are also clear links between specific GRCs (e.g., gambling related positive expectancies) and greater psychological distress in the form of depression and anxiety (Ciccarelli et al, 2017). These associations also seem to appear in a variety of cultural contexts, with studies of gamblers in Italy demonstrating links between GRCs and a variety of distress indicators such as anxiety, depression, and neuroticism (Iliceto et al, 2015). Similarly, in a Turkish sample, such cognitions were associated with greater negative affect (Arcan & Karanci, 2015).…”
Section: Gambling Related Cognitionsmentioning
confidence: 95%
“…Similarly, there are also clear links between specific GRCs (e.g., gambling related positive expectancies) and greater psychological distress in the form of depression and anxiety (Ciccarelli et al, 2017). These associations also seem to appear in a variety of cultural contexts, with studies of gamblers in Italy demonstrating links between GRCs and a variety of distress indicators such as anxiety, depression, and neuroticism (Iliceto et al, 2015). Similarly, in a Turkish sample, such cognitions were associated with greater negative affect (Arcan & Karanci, 2015).…”
Section: Gambling Related Cognitionsmentioning
confidence: 95%
“…Additional studies of the GRCS have led to creation and validation of Italian (Iliceto et al, 2015), Turkish (Arcan & Karanci, 2015), and Chinese (Oei et al, 2007) versions of the measure (with the original factor structure supported in these subsequent studies). Higher GRCS scores have been found to be associated with problem gambling (Cosenza, Baldassarre, Matarazzo, & Nigro, 2014;Marmurek, Switzer, & D'Alvise, 2014, the increased likelihood of relapse in problem gambling , neuroticism (Iliceto et al, 2015), and "proneness to delusion" (Abdollahnejad, Delfabbro, & Denson, 2015). The initial validation report indicated significant gender differences on GRCS total scores and all subscales except illusion of control (Raylu & Oei, 2004).…”
Section: Fallacy Instruments?mentioning
confidence: 99%
“…With regard to the concurrent validity of the scale, the authors found significant correlations between GRCS total scores and the SOGS (r = 0.43). Recent research showed good psychometric properties of the Italian version of the GRCS (GRCS-I) in a sample of 511 adults from the Italian community, including reliability (Cronbach's alpha = 0.85) and concurrent validity with respect to the SOGS (Pearson's product-moment correlation coefficients were 0.56 for the GRCS total and 0.51, 0.38, 0.42, 0.50, and 0.49 for the five subscales, respectively) (Iliceto et al 2015).…”
Section: Instrumentsmentioning
confidence: 99%
“…The authors developed and validated the Gambling-Related Cognitions Scale (GRCS) to measure gambling-related cognitions. The scale has very good psychometric properties and has been translated and validated in a number of languages and cultural contexts, including Italy (Iliceto et al 2015). A number of studies found that problem gamblers are more likely to activate gambling-related cognitions than non-problem players and non-gamblers Joukhador et al 2003;Toneatto 1999;Walker 1992).…”
mentioning
confidence: 99%